Care maps are an effective tool for optimizing quality of care of infectious diseases in a resource-constrained short-stay ambulatory care setting. Issue 5 (5th February 2021) - Washirasaksiri, Chaiwat; Phisalprapa, Pochamana; Chaisathaphol, Thanet; Auesomwang, Chonticha; Sitasuwan, Tullaya; Tinmanee, Rungsima; Kositamongkol, Chayanis; Sutee, Rungsinee; Chouriyagune, Charoen; Srivanichakorn, Weerachai
Abstract : Abstract: Care maps (CMs), which are innovative, comprehensive, educational, and simple medical tools, were developed for 6 common diseases, including heart failure, stroke, hyperglycemia, urinary tract infection, dengue infection, and upper gastrointestinal bleeding, were implemented in a short-stay ambulatory ward. This study aimed to investigate the effectiveness of and level of clinician satisfaction with CMs in an ambulatory care setting. A retrospective chart review study comparing the quality of care between before and after CM implementation was conducted. The medical records of patients who were admitted to a short-stay ambulatory ward in a tertiary referral center were reviewed. Demographic data, severity of disease, quality of care, length of stay (LOS), admission cost, and CM user satisfaction were collected and recorded. The medical records of 1116 patients were evaluated. Of those, 589 and 527 patients were from before (non-CM group) and after CM (CM group) implementation, respectively. There were no significant differences between groups for age, gender, or disease-specific severity the median (interquartile range) total and essential quality scores were significantly higher in the CM group than in the non-CM group [total quality score 85.3 (75.0–92.9) vs 61.1 (50.0–75.0); P  < .001, and essential quality scores 90.0 (75.0–100.0) vs 60.0 (40.6–80.0); P  < .0001, respectively]. All aspects of quality of care were significantly improved between before and after CM implementation. Overall median LOS was significantly decreased from 3.8 (2.5–5.7) to 3.0 (2.0–4.9) days, but there was no significant decrease for admission cost. However, CMs were able to significantly reduce both LOS and admission cost in the infectious disease-related subgroup. Most CM users reported satisfaction with CMs. CMs were shown to be an effective tool for improving the quality of care in patients with ambulatory infectious diseases. In that patient subgroup, LOS and admission cost were both significantly reduced compared to pre-CM implementation. Abstract : Supplemental Digital Content is available in the text